Formative Research to Develop a Lifestyle Application (App) for African American Breast Cancer Survivors - Selina Smith; Mary Whitehead; Joyce Sheats; Brittney Fontenot; Ernest Alema-Mensah; Benjamin Ansa (Georgia Southern University, 2016)
Background: There is a proliferation of lifestyle-oriented mobile technologies; however, few have targeted users. Through intervention mapping, investigators and community partners completed Steps 1-3 (needs assessment, formulation of change objectives, and selection of theory-based methods) of a process to develop a mobile cancer prevention application (app) for cancer prevention. The aim of this qualitative study was to complete Step 4 (intervention development) by eliciting input from African American (AA) breast cancer survivors (BCSs) to guide app development. Methods: Four focus group discussions (n=60) and three individual semi-structured interviews (n=36) were conducted with AA BCSs (40-72 years of age) to assess barriers and strategies for lifestyle change. All focus groups and interviews were recorded and transcribed verbatim. Data were analyzed with NVivo qualitative data analysis software version 10, allowing categories, themes, and patterns to emerge. Results: Three categories and related themes emerged from the analysis: 1) perceptions about modifiable risk factors; 2) strategies related to adherence to cancer prevention guidelines; and 3) app components to address barriers to adherence. Participant perceptions, strategies, and recommended components guided development of the app. Conclusions: For development of a mobile cancer prevention app, these findings will assist investigators in targeting features thatare usable, acceptable, and accessible for AA BCSs.